Comparison of Learning Achievement Physics Education Students, FKIP- Unsyiah in Senior High School and Higher Education - Ahmad Farhan; D Fitriyani Dalimunthe; Agus Wahyuni; Evendi Evendi; Nurul Wati (Asian Journal of Science Education, 2020)
Based on cognitive maturity, students of the Physics Education Department, Teacher Training and Education Faculty - Unsyiah when they were at the education level in Senior High School and College were in the same category, namely the early adult stage. That requires students could adjust to the pattern of learning life in higher education, especially first-year students who are in a transition period from high school to college. The purpose of this study was to compare whether the learning achievements obtained by Physics Education Students, Teacher Training and Education Faculty - Unsyiah were better than the achievements achieved at Senior High Schools. This type of research is a comparative study with a quantitative approach. The sampling technique used purposive sampling with a sample of 37 students of class 2018. The data was collected using the documentation method. Data were analyzed using the t-test equation. From the analysis, it can be seen that the results of the hypothesis test obtained are the t count = 7.05 with a significant level of α = 0.05 and t table = 1.68, so the results are rejected H0 and accept Ha because of t count ≥ t table. It was concluded, that the learning achievement of Physics Materials from Physics Education Students, Teacher Training and Education Faculty - Unsyiah in the college was better than during high school.